Portfolio Choice over the Life‐Cycle when the Stock and Labor Markets Are Cointegrated - BENZONI, LUCA; COLLIN‐DUFRESNE, PIERRE; GOLDSTEIN, ROBERT S. (Journal of Finance, 2007)
ABSTRACT We study portfolio choice when labor income and dividends are cointegrated. Economically plausible calibrations suggest young investors should take substantial short positions in the stock market. Because of cointegration the young agent's human capital effectively becomes “stock‐like.” However, for older agents with shorter times‐to‐retirement, cointegration does not have sufficient time to act, and thus their human capital becomes more “bond‐like.” Together, these effects create hump‐shaped life‐cycle portfolio holdings, consistent with empirical observation. These results hold even when asset return predictability is accounted for.